Carta de Roberto H. Todd a Juan R. Baiz - Todd, Roberto H.; Baiz, Juan R. (My University, 1911)
Documentos relacionados a la Comisión de la Policía Insular.
Keywords: Policía--Puerto Rico.; Police--Puerto Rico.; Puerto Rico. Insular Police.; Puerto Rico. Policía Insular.